A better normal in Canada will need a better detection system for emerging and re-emerging respiratory pathogens - Berry, Isha; Brown, Kevin A.; Buchan, Sarah A.; Hohenadel, Karin; Kwong, Jeffrey C.; Patel, Samir; Rosella, Laura C.; Mishra, Sharmistha; Sander, Beate (Canadian Medical Association journal (CMAJ), 2022)
Berry et al propose a tiered surveillance approach that encompasses waste-water testing, representative population-based testing (including data on potential transmission mechanisms; e.g., social determinants of health) and genomics to efficiently monitor disease trends, and rapidly detect resurgences and emergence of novel variants or strains. This information is crucial to inform the development of tailored and effective public health programs. The proposed system could, and ultimately should, be expanded beyond COVID-19 to support pan-respiratory pathogen surveillance.